2016
DOI: 10.1016/j.amjmed.2016.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Back to the Future: Penicillin-Susceptible Staphylococcus aureus

Abstract: More than one-quarter of patients with MSSA bacteremia potentially could be treated with parenteral penicillin, which may offer pharmacokinetic advantages over other beta-lactam drugs and potentially improved outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…In contrast with the extensive efforts to characterize MRSA, only a small number of studies have characterized the dynamics of all S. aureus subtypes, possibly due to the expectation that prevalence of penicillin susceptible S. aureus (PSSA) is extremely low 23 . However, recent reports from diverse sites describe a rising or surprisingly high prevalence of PSSA [24][25][26][27] . Whether this trend is associated with the decline in MRSA and how it impacts overall rates of S. aureus infection are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with the extensive efforts to characterize MRSA, only a small number of studies have characterized the dynamics of all S. aureus subtypes, possibly due to the expectation that prevalence of penicillin susceptible S. aureus (PSSA) is extremely low 23 . However, recent reports from diverse sites describe a rising or surprisingly high prevalence of PSSA [24][25][26][27] . Whether this trend is associated with the decline in MRSA and how it impacts overall rates of S. aureus infection are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…R ecent publications have reported on the rise of penicillin-sensitive Staphylococcus aureus (PSSA). This trend has now been observed on several continents (1) and has been shown to involve bloodstream infections and other serious infections (2). This increase in the incidence of PSSA infections has also been mirrored by a decrease in methicillin-resistant S. aureus (MRSA) infection rates (3), which raises two important questions.…”
mentioning
confidence: 99%
“…The increasing isolation of CA‐MRSA from patients in healthcare settings has begun to blur the clinical distinction between HA‐MRSA and CA‐MRSA (Bal et al ., ). The widespread emergence of β‐lactamase producing S. aureus isolates rendered early penicillin‐type antibiotics largely ineffective (although several recent studies have revealed that with the cessation of penicillin usage clinically, non‐β‐lactamase producing/penicillin‐susceptible S. aureus strains are being more frequently isolated (Crane, ; Chabot et al ., ; Cheng et al ., )). This therapeutic problem was temporarily abated in the 1960s with the introduction of methicillin, which is resistant to β‐lactamase‐mediated hydrolysis.…”
Section: Opportunistic Pathogen Extraordinairementioning
confidence: 99%